Evidence for intermolecular domain exchange in the Fab domains of dimer and oligomers of an IgG1 monoclonal antibody. Issue 6 (18th August 2017) - Luo, Yin; Raso, Stephen W.; Gallant, Judith; Steinmeyer, Colleen; Mabuchi, Yasuko; Lu, Zhaojiang; Entrican, Clifford; Rouse, Jason C.
ABSTRACT: Recombinant protein therapeutics have become increasingly useful in combating human diseases, such as cancer and those of genetic origin. One quality concern for protein therapeutics is the content and the structure of the aggregated proteins in the product, due to the potential immunogenicity of these aggregates. Collective efforts have led to a better understanding of some types of protein aggregates, and have revealed the diversity in the structure and cause of protein aggregation. In this work we used a broad range of analytical techniques to characterize the quinary structure (complexes in which each composing unit maintains native quaternary structure) of the stable non-covalent dimer and oligomers of a monoclonal IgG1λ antibody. The results supported a mechanism of intermolecular domain exchange involving the Fab domains of 2 or more IgG molecules. This mechanism can account for the native-like higher order (secondary, tertiary and disulfide bonding) structure, the stability of the non-covalent multimers, and the previously observed partial loss of the antigen-binding sites without changing the antigen-binding affinity and kinetics of the remaining sites (Luo et al., 2009, mAbs 1:491). Furthermore, the previously observed increase in the apparent affinity to various Fcγ receptors ( ibid ), which may potentially promote immunogenicity, was also explained by the quinary structure proposed here. Several lines of evidence indicated that the formation of multimers by the mechanism of intermolecular domain exchange took place mostly during expression, not in the purified materials. The findings in this work will advance our knowledge of the mechanisms for aggregation in therapeutic monoclonal antibodies.